Association with AflR in Endosomes Reveals New Functions for AflJ in Aflatoxin Biosynthesis - Ehrlich, Kenneth C. (MDPI, 2012)
Aflatoxins are the most potent naturally occurring carcinogens of fungal origin. Biosynthesis of aflatoxin involves the coordinated expression of more than 25 genes. The function of one gene in the aflatoxin gene cluster, aflJ, is not entirely understood but, because previous studies demonstrated a physical interaction between the Zn(2)Cys(6) transcription factor AflR and AflJ, AflJ was proposed to act as a transcriptional co-activator. Image analysis revealed that, in the absence of aflJ in A. parasiticus, endosomes cluster within cells and near septa. AflJ fused to yellow fluorescent protein complemented the mutation in A. parasiticus ΔaflJ and localized mainly in endosomes. We found that AflJ co-localizes with AflR both in endosomes and in nuclei. Chromatin immunoprecipitation did not detect AflJ binding at known AflR DNA recognition sites suggesting that AflJ either does not bind to these sites or binds to them transiently. Based on these data, we hypothesize that AflJ assists in AflR transport to or from the nucleus, thus controlling the availability of AflR for transcriptional activation of aflatoxin biosynthesis cluster genes. AflJ may also assist in directing endosomes to the cytoplasmic membrane for aflatoxin export.